Determining Seasonal Spatial and Temporal Distribution of Chlorophyll-a, and its Concentration in Kuwait and the Arabian Gulf using Satellite and In-situ Data - Albanai, Jasem (Transactions on Maritime Science, 2024)
As an indicator of phytoplankton density in an area, the concentration of chlorophyll-a (Chl-a) is an important reflection of marine water quality. Remote sensing techniques have been developed to measure the near-surface concentration of Chl-a in water by combining spectral bands and in situ data. This algorithm can be applied to sensors of varying spatial, temporal and spectral resolutions. However, in this study, Chl-a level 2 and 3 products of SNPP – VIIRS spectrometer (Equation OC3) from NASA’s OceanColor suite were relied upon to establish the spatial and temporal distribution of Chl-a concentration in the Arabian Gulf (also known as the Persian Gulf) and the territorial waters of the State of Kuwait (located in the north-eastern part of the Arabian Gulf) in 2012-2019. Ground truthing points (n = 192) matched with level 2 products have been used to build and cross-validate an empirical model. The correlation was positive, with r^2 = 0.79 and validation RMSE = ± 0.64 mg/m-3. The derived algorithm was then applied to Chl-a level 3 seasonal products. Additionally, the Chl-a concentration values in Kuwaiti waters were enhanced using the IDW algorithm to increase spatial resolution, given its small size compared to the spatial resolution of level 3 Chl-a products. The model derived from IDW was tested using the Mann Whitney test (Sig = 0.948 p > 0.01). However, the result showed that Chl-a concentration was higher in the Kuwait Bay (average = 2.8 mg/m-3) than in Kuwaiti waters (average = 2.3 mg/m-3), and higher in Kuwaiti waters (average = 2.1 mg/m-3) than in the Arabian Gulf (average = 0.7 mg/m-3). Coasts have higher concentrations than open water. Generally, the Chl-a increases in winter and had a semi-regular cycle during the years of study; this cycle is more regular in the Gulf than in Kuwait.